Synthesis and growth mechanism of whisker‐like Mg2B2O5 crystals by an easy and environmentally hospitable non‐aqueous ionic liquid method. (1st February 2015) - Wang, Wenzhong; Wang, Jun; Deng, Ao; Wang, Lijuan; Shi, Honglong; Liang, Yujie
Abstract : An environmentally hospitable NaCl non‐aqueous ionic liquid method has been employed to prepare single crystalline whisker‐like Mg2 B2 O5 crystals, which were synthesised by annealing a ground mixture of H3 BO3, MgCl2 ·6H2 O, NaCl and surfactant nonylphenyl ether (9) at 850°C for 2 h. The systemically comparative experiments have been performed to understand the formation mechanism of whisker‐like Mg2 B2 O5 crystals. The results demonstrated that both non‐aqueous ionic liquid and nonylphenyl ether (9) played vital roles in the formation of whisker‐like Mg2 B2 O5 crystals. Based on the experimental results and analysis, a reasonable growth mechanism of whisker‐like Mg2 B2 O5 crystals is proposed. This reported work opens up a relative low‐temperature strategy for the synthesis of single crystalline whisker‐like Mg2 B2 O5 crystals.